2020
DOI: 10.1038/s41598-020-69017-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and disease burden of respiratory syncytial virus infection among hospitalized adults

Abstract: the disease burden of respiratory syncytial virus (RSV) infection in the adult population has not been well characterized compared to children. investigation of the clinical characteristics and disease burden of adult RSV infection would help to establish public health policy and a future vaccine strategy. We retrospectively collected medical records of hospitalized adult patients who were diagnosed with RSV infection from January 2012 to December 2015 from three tertiary hospitals. Baseline characteristics, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
36
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 25 publications
5
36
4
Order By: Relevance
“…We found that clinical features associated with RSV, hMPV, and influenza virus infections were largely similar to one another, although certain features did differ between these three infection types. Consistent with prior study results, we found that patients with RSV and hMPV infections were more likely to be older and to suffer from underlying systemic diseases such as cancer [30,31]. The presence of myalgia was more often associated with influenza [32,33], whereas nasal congestion and dyspnea were more closely linked to RSV infection [34,35].…”
Section: Discussionsupporting
confidence: 89%
“…We found that clinical features associated with RSV, hMPV, and influenza virus infections were largely similar to one another, although certain features did differ between these three infection types. Consistent with prior study results, we found that patients with RSV and hMPV infections were more likely to be older and to suffer from underlying systemic diseases such as cancer [30,31]. The presence of myalgia was more often associated with influenza [32,33], whereas nasal congestion and dyspnea were more closely linked to RSV infection [34,35].…”
Section: Discussionsupporting
confidence: 89%
“…We found that clinical features associated with RSV, hMPV, and in uenza virus infections were largely similar to one another, although certain features did differ between these three infection types. Consistent with prior study results, we found that patients with RSV and hMPV infections were more likely to be older and to suffer from underlying systemic diseases such as cancer [30][31]. The presence of myalgia was more often associated with in uenza [32][33], whereas nasal congestion and dyspnea were more closely linked to RSV infection [34][35].…”
Section: Discussionsupporting
confidence: 88%
“…As in other studies, cancer and immunosuppression tended to be more common among RSV than influenza patients; however, these differences did not reach statistical significance, and the lack of patients with acute hematologic malignancies or recent transplant may have affected our results 20,21,33 . Another recent study reported that hematologic malignancies and solid cancer are risk factors of RSV pneumonia 38 …”
Section: Discussioncontrasting
confidence: 51%
“… 20 , 21 , 33 Another recent study reported that hematologic malignancies and solid cancer are risk factors of RSV pneumonia. 38 …”
Section: Discussionmentioning
confidence: 99%